Effect of gender, muscle type and skinfold thickness on myometric parameters in young people - Joanna Mencel (PeerJ Inc., 2021)
Background The aim of the study was to compare the mechanical properties of three human skeletal muscles: biceps brachii (BB), rectus femoris (RF), and tibialis anterior (TA) at rest measured by myoton device in males (n = 16, mean age 21.2 ± 0.6 years) and females (n = 16; 21.2 ± 0.9 years) and to investigate the influence of skin and subcutaneous tissue thickness (skinfold thickness, SFT) and gender on myometric parameters of the three skeletal muscles. Methods We measured the following mechanical and viscoelastic muscle properties using MyotonPRO®: frequency (F [Hz]), decrement (D [log]), stiffness (S [N/m]), relaxation time (R [ms]) and creepability (C [De]). The values of SFT for all selected muscles were assessed by caliper. A mixed-design analysis of variance with gender as between subject comparison was used for assessing the differences between gender and muscles in SFT and each of the myometric parameters separately (F, D, S, R and C). Pearson correlation coefficient or Spearman’s rank correlation coefficient between SFT and myometric parameters was conducted for males, females and males and females together. The level of statistical significance was set at α ≤ 0.05 with Bonferroni correction for multiple comparisons. Results The SFT over the RF, TA, and BB muscles in women was statistically significantly larger compared with that of males. In females and males, the SFT over the RF was larger than over the TA and BB, and the SFT over the TA was larger compared with over the BB. The values of F and S recorded for the TA muscle were the highest among the three muscles, while D, C, and R were lowest in TA but highest in the RF muscle in men and women. The values of F and S were smaller in females than in males. Gender comparison of D, C, and R values showed that only D for the RF was significantly lower in females than in males, and C for the RF and TA was significantly larger in females than in males. Some correlation between SFT and myometric parameters were different between males and females. For example, there was a significant, negative correlation between SFT and F for all muscles in females, and a significant, positive correlation between these parameters for BB and TA (not for RF) in males. For pooled data (males and females together), a negative significant correlation between SFT and F was observed for RF and TA (not significant for BB muscle). Discussion It is concluded that the TA compared with the BB and RF has significantly greater F and S but the smallest D and C and the shortest R. Gender and muscle differences in the SFT may affect the measurements of muscle properties using MyotonPRO®. The relationship between SFT and myometric parameters is different in males and females in the RF, TA, and BB muscles. Therefore, the myometric data should be analyzed in males and females separately.